Consequences of aerobic resistance exercise combined with Liprimar in the treatment of Chronic obstructive pulmonary disease : Liprimar and aerobic resistance exercise on lung function - Liu, Yanping; Wang, Huiyao; Nie, Bingjie; Liu, Yahua (Progress in Nutrition, 2021)
Abstract. Background: Aerobic resistance exercise is fundamentally required for the patients with COPD at a stable stage, to recover their exercise function. While the patients need to be supplemented with medication as well to inhibit the production of inflammatory factors. Atorvastatin calcium (a derivative of Atorvastatin) is reported as component in Liprimar. However, there are only few studies available on the treatment of COPD by Liprimar. The current study investigates the therapeutic value of aerobic resistance exercise, combined with Liprimar, in treating COPD patients and attempts to provide a basis for the treatment of COPD. Methods: The author(s) recruited a total of 147 patients diagnosed with COPD and were hospitalized at Internal medicine department, Third Clinical Medical College, Xinjiang Medical University (Cancer Hospital) and the study period was between October 2015 and June 2019. 120 patients were selected as subjects of this experiment on a voluntary basis. Aerobic resistance exercise therapy, Liprimar and combination therapy were provided to the patients. The patients’ physical fitness indicators, levels of inflammatory cytokines and cardiopulmonary function were observed to evaluate the treatment plan. Results: The COPD patients who received aerobic and obstructive exercise treatment, in combination with Liprimar, showed improvement in the indicators related to physical fitness, decreased body fat percentage, waist-to-hip ratio, BMI, blood sugar, Hba1c content, blood lipid, low levels of inflammatory factors (such as IL-8, IL-6, TNF-α), and notable recovery in cardiopulmonary function. Conclusions: A combination of aerobic and obstructive exercises with Liprimar can treat COPD patients in a better way. It can improve the exercise function and cardiopulmonary function of the patients. However, the clinical application of this treatment plan should be verified with more sample size. Further, the clinical application should also adjust the plan appropriately, according to individual differences.